The Deep Learning Revolution: Transforming Indonesia's Education System Towards the Digital Era 2025: Revolusi Pembelajaran Mendalam: Transformasi Sistem Pendidikan Indonesia Menuju Era Digital 2025 - Nabila Hilyatunisa (Yayasan Cerdas Pedia Indonesia, 2025)
This study analyzes the deep learning revolution in transforming Indonesia's education system toward the digital era 2025. Through a systematic literature review using Scopus database covering 2015-2025, this research identifies semantic ambiguity surrounding